Nonsurgical molding of congenital auricular deformities and analysis of the correction outcomes: A single-center, retrospective study in east China - Liu, Chuanbo; Wo, Peibin; Zhang, Jufang; Li, Jinsheng (Frontiers in Pediatrics, 2022)
Objective Our research was carried out to provide a clinical reference for the application of nonsurgical therapy in newborns with congenital auricular deformities in east China. Methods A retrospective study of consecutive newborns using noninvasive ear molding was conducted in Hangzhou in east China's Zhejiang Province. The demographic and clinical information and photographs of the ear before and after treatment were taken. The diagnosis of each auricular deformity was identified, and the treatment outcome was evaluated. Results A total of 224 patients including 356 congenital ear anomalies received noninvasive ear molding. The median age of infants to initiate treatment was 39.5 days. The median treatment duration was 42.5 days. The median follow-up time was 137.0 days. The overall treatment effective rate of all infants with nonoperative ear molding was 92.1%, and mild skin irritation and ulceration occurred in 34 ear deformities (9.6%). It confirmed that the treatment efficiency was satisfactory and the complication rate was still acceptable despite the late initiation treatment of neonates in east China. Further analysis of treatment outcomes among three subgroups of infants (the ages to initiate the ear molding were respectively less than or equal to 28, 29–56, and more than 57 days) revealed that initiation treatment was significantly related to the treatment results and the earlier the initiation treatment, the higher the effective rate and the lower the complication incidence. Conclusion Our study hints that newborns in east China may have a longer period for correction. What is more, although our study affirmed a longer period for noninvasive molding, early diagnosis and treatment are still recommended to improve therapy efficiency and reduce treatment duration and complications.